FACTORS AND PRINCIPLES OF FORMATION OF LEGAL CULTURE OF DISABLED PRIMARY STUDENTS (Web of Discoveries: Journal of Analysis and Inventions, 2023)
This article describes the current issues of forming the legal culture of children with disabilities, the requirements and principles for the process of forming legal culture in educational activities.